Co-production: The State of the Art in Research and the Future Agenda - Verschuere, Bram; Brandsen, Taco; Pestoff, Victor (Voluntas (Manchester, England), 2012)
In this introductory article to the thematic issue, our aim is to discuss the state of the art in research on co-production of public services. We define co-production, for the purpose of this article rather narrowly, as the involvement of individual citizens and groups in public service delivery. We discuss the concept along three main research lines that emerge from the literature: what are the motives for co-production? How can co-production be organized effectively? What are the effects of co-production? Secondly, we also critically assess the state of the art and discuss some conceptual and methodological issues that are still open to debate. Thirdly, we propose some directions for future research: greater methodological diversity and the need for empirical and comparative research with a specific attention for theoretical advancement in co-production research. Dans cet article d'introduction à la question thématique, notre objectif est de discuter le pointe de la dans la recherche sur la coproduction des services publics. Nous définissons la coproduction, dans le but de cet article plutôt étroite, comme la participation des citoyens et des groupes dans la prestation des services publics. Nous discutons du concept le long de trois lignes de recherche principales qui se dégagent de la littérature : quels sont les motifs de coproduction ? Comment pouvez coproduction être organisée efficacement ? Quels sont les effets de coproduction ? Deuxièmement, nous avons aussi critique évaluer l'état de l'art et discuter de certains problèmes conceptuels et méthodologiques qui sont encore ouverts au débat. Troisièmement, nous proposons quelques orientations pour la recherche future : une plus grande diversité méthodologique et la nécessité pour la recherche empirique et comparative avec une attention spécifique d'avancement théorique dans la recherche de la coproduction. In diesem einführenden Artikel zur thematischen Ausgabe ist unser Ziel, dem von der Stand in der Forschung auf Koproduktion der öffentlichen Dienstleistungen zu diskutieren. Wir definieren Koproduktion im Sinne dieses Artikels ziemlich eng, als die Beteiligung der einzelnen Bürger und Gruppen in öffentlichen Dienstleistungen. Wir diskutieren das Konzept entlang drei Forschungsschwerpunkte-Linien, die von der Literatur entstehen: Was sind die Motive für Koproduktion? Wie kann die Koproduktion effektiv werden organisiert? Was sind die Auswirkungen der Co-Produktion? Zweitens, wir auch kritisch bewerten den Stand der Technik und diskutieren einige konzeptionelle und methodische Probleme, die noch offen zu diskutieren sind. Drittens schlagen wir eine Wegbeschreibung für die künftige Forschung: größere methodische Vielfalt und die Notwendigkeit für die empirische und vergleichende Forschung mit einer besonderen Aufmerksamkeit für die theoretische Weiterentwicklung in Co-Produktion-Forschung En este artículo introductorio a la cuestión temática, nuestro objetivo es debatir el estado de la arte en investigación en coproducción de los servicios públicos. Definimos la coproducción, con el propósito de este artículo bastante restringida, como la participación de los ciudadanos individuales y grupos en la prestación de servicios públicos. Discutimos el concepto a lo largo de los tres principales líneas de investigación que surgen de la literatura: ¿Cuáles son los motivos para la coproducción? ¿Cómo puede coproducción organizarse eficazmente? ¿Cuáles son los efectos de la coproducción? En segundo lugar, que también críticamente evaluar el estado del arte y discutir algunos problemas conceptuales y metodológicos que siguen abren al debate. En tercer lugar, proponemos algunas direcciones para futuras investigaciones: mayor diversidad metodológica y la necesidad de una investigación empírica y comparativa con una atención específica para avance teórico en la investigación de coproducción.